Risk prediction score and appendicectomy in the elderly: a single centre 5‐year retrospective cohort study. Issue 10 (21st July 2021) - Farkas, Nicholas; Harris, Holly; Conroy, Michael; Kenny, Ross; Bickford, Benjamin; Baig, Mirza
Abstract: Background: Appendicitis is a common surgical emergency that can be a challenging entity to manage. In the elderly, it is associated with significant morbidity and mortality. Risk prediction is not routinely performed prior to surgery. Methods: All patients aged >65 years undergoing appendicectomy over 5 years from one NHS Trust were included. Age, American Society of Anesthesiologists physical status classification system (ASA grade), Rockwood score, type of surgery, length of stay, morbidity and 90‐day mortality were recorded. ACS NSQIP was retrospectively calculated. Spearman's Rank correlation coefficient and linear regression analysis were conducted, assessing correlation between ASA, Age, Rockwood Score and ACS NSQIP with length of stay and post‐operative complications. Results: A total of 225 patient cases were reviewed. A complication rate of 29.3% was recorded, with a 6.7% serious complication rate. Two mortalities occurred. ASA, Age, Rockwood and NSQIP scoring systems all showed low degree positive correlation with length of stay (+0.16–+0.34). As predictors of length of stay, ASA was superior. Rockwood and age showed low degree positive correlation (+0.25–+0.33) with post‐operative complications. NSQIP and ASA demonstrated a greater degree of correlation (+0.38–+0.40). Conclusion: Both ASA and ACS NSQIP appear superior indicators for outcomes compared to age and Rockwood score. However, caution is warranted when interpreting the superiority of ASA over validated risk stratification tools. Therefore, we advocate the use of pre‐operative risk stratification for elderly patients undergoing low‐risk surgery such as appendicectomy. Validated tools are not routinely applied in many centres currently. Utilisation of scores such as ACS NSQIP may help improve consent, patient selection, outcomes and expectations. Abstract : Appendicitis is a common surgical emergency in the elderly. We review the correlation between ASA, Age, Rockwood Score and ACS NSQIP with length of stay and post‐operative complications. We found ASA and NSQIP to have a greater degree of correlation than other methods. Utilisation of risk prediction scores may help improve consent, patient selection, outcomes and expectations.